2
$\begingroup$

In the book An Introduction to Quantum Field Theory by Michael E. Peskin and Daniel V. Schroeder, they derive the Callan-Symanzik equation for the two-point function

\begin{equation} \left[M\frac{\partial}{\partial M}+\beta(\lambda)\frac{\partial}{\partial \lambda}+2\gamma(\lambda)\right]G^{(2)}(p)=0 \end{equation}

Then they want to change variable from $M$ to $p$ with space-like momentum $p=\sqrt{-p^2}$ and they find out (pg. 418) that

\begin{equation} \left[p\frac{\partial}{\partial p}-\beta(\lambda)\frac{\partial}{\partial \lambda}+2-2\gamma(\lambda)\right]G^{(2)}(p)=0 \end{equation}

I don't understand where the $+2$ came from. I did all the calculation, i found the overall minus sign, but i couldn't find out the origin of the factor $+2$.

Any Ideas?

$\endgroup$
3
$\begingroup$

I think it goes more or less as follows:

As written in the book the dependence of the two-point function on $p$ and $M$ reduces to $$G^{(2)}(p)=\frac{i}{p^2}g(-p^2/M^2).$$

Therefore one has $$p\frac{\partial G^{(2)}(p)}{\partial p}=-2G^{(2)}(p)-\frac{2i}{M^2}g'(-p^2/M^2)$$ Which follows just from the product rule of derivatives (where I have taken $i/p^2$ as first factor and $g(-p^2/M^2)$ as the second factor.) and the definition of $G^{(2)}(p)$ above. On the other hand $$M\frac{\partial G^{(2)}(p)}{\partial M}=\frac{2i}{M^2}g'(-p^2/M^2).$$ Now one can use the two equation to eliminate $g'$ and express derivatives w.r.t. $M$ in terms of derivatives w.r.t. $p$: $$M\frac{\partial G^{(2)}(p)}{\partial M}=-p\frac{\partial G^{(2)}(p)}{\partial p}-2G^{(2)}(p)$$ or $$M\frac{\partial }{\partial M}=-p\frac{\partial }{\partial p}-2$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.